The Use of Probability Inequalities in Multiproduct C-V-P Analysis Under Uncertainty - Johnson, Glenn L.; Simik, S. Stephen (Journal of Accounting Research, 1974)
C-V-P Analysis, Cost-Value-Profit analysis, Upper boundaries